Evaluation of knowledge and conduct of doctors and dentists on violence against children and adolescents - Aguiar, Sandra Maria Herondina Coelho Ávila; Souza, Eduardo Antonio (ARCHIVES OF HEALTH INVESTIGATION, 2016)
Violence against children is spreading, regardless of ethnic group, age, social class, gender or color. Because of lack of awareness, reports statistics and negligence of the population, violence that includes mistreatment, negligence and sexual abuse that could kill reaches a level of no concern coming from health professionals, highlighted by this study. On evaluating the awareness that physicians and dentists have about mistreatment by using questionnaires, the authors conclude that these professionals knew about the issue, recognized the characteristic signs and symptoms of abused children and the ones who cause them. However Children Care Organizations do not know how to document the evidences and when they have a suspect of the fact but they do not make a report. The author also emphasizes that the under-graduate courses are not lecturing about this subject. Descriptors: Child Abuse; Domestic Violence; Negligence; Awareness; Dentists; Physicians.